Keabsahan Perkawinan yang Dilaksanakan dengan Ayah Tiri sebagai Wali Nikah Berdasarkan Kompilasi Hukum Islam dan Undang-Undang Nomor 16 Tahun 2019 Tentang Perkawinan - Amanda Prasxilia Chairunesa (Bandung Conference Series: Law Studies, 2023)
Abstract. Guardian in marriage is one of the conditions that causes the process of a marriage to be valid, a person must meet certain criteria to be able to become a guardian in a marriage. The lack of awareness of the importance of the guardian's position in marriage has resulted in several marriages being invalid by law due to the invalid guardianship. Guardians can be represented by way of taukil, this is referred to as a representative guardian. The purpose of this study is to determine the validity of marriages that are represented by stepfathers in terms of aspects of Islamic law and also Law Number 16 of 2019 concerning Marriage. and to find out the legal consequences of marriages that are represented by stepfathers based on Islamic law and laws Number 16 of 2019 concerning Marriage. This research method uses a juridical-normative approach, and this research is descriptive analysis in nature. The data collection technique used was document study and by conducting interviews, and the data that had been obtained was analyzed in a qualitative juridical manner. Marriage will be said to be valid if the guardian is someone who has a lineage or blood line with certain conditions as stated in Article 21 KHI. If the order of guardians in Article 21 KHI does not want the guardianship process, they have the right to give the guardian's will to the judge's guardian to become the bride's marriage guardian provided that the nasab guardian has agreed that if the guardian of the marriage is the judge's guardian, his guardianship status is valid. , then the marital status will be valid. In addition to the nasab guardian giving permission to the judge's guardian, there are also other guardians who do not have blood ties or straight lineage and above, can become marriage guardians on condition that they have a taukil letter given by the original guardian to the representative guardian. Original evidence witnessed by 2 witnesses. With a taukil letter or pronouncement of a guardian's representative from the original guardian to another person who is not related by blood or straight line upwards, then the guardian's representative is valid to become the bride's marriage guardian, then regarding the marital status represented by the guardian's representative will be valid. Abstrak. Wali dalam perkawinan merupakan salah satu syarat yang menyebabkan proses suatu perkawinan menjadi sah, seseorang harus memenuhi kriteria tertentu untuk dapat dijadikan wali dalam sebuah perkawinan. Lengahnya kesadaran akan pentingnya kedudukan wali di perkawinan mengakibatkan beberapa perkawinan menjadi tidak sah hukumnya karena hal wali yang tidak sah. Wali dapat diwakilkan dengan cara taukil, hal ini disebut sebagai wakil wali. Adapun tujuan penelitian ini adalah Untuk mengetahui keabsahan perkawinan yang diwalikan oleh ayah tiri yang ditinjau dari aspek hukum Islam dan juga Undang-Undang Nomor 16 Tahun 2019 tentang Perkawinan.dan untuk mengetahui konsekuensi hukum dari perkawinan yang diwalikan ayah tiri berdasarkan hukum islam dan Undang-Undang Nomor 16 Tahun 2019 tentang Perkawinan. Metode penelitian ini menggunakan metode pendekatan Yuridis-Normatif, dan penelitian ini bersifat deskriptif analisis. Teknik pengumpulan data yang digunakan adalah studi dokumen dan dengan melakukan wawancara, serta data yang sudah diperoleh dianalisis secara yuridis kualitatif. perkawinan akan dikatakan sah apabila yang mnejadi wali adalah yang memiliki nasab garis keatas atau sedarah dengan ketentuan tertentu seperti pada Pasal 21KHI. Jika urutan wali dalam Pasal 21 KHI tersebut tidak menghendaki dalam proses perwalian, mereka berhak untuk memberikan kehendak wali kepada wali hakim untuk menjadi wali nikah mempelai wanita dengan ketentuan bahwa wali nasab telah sepakat jika yang akan menjadi wali nikah adalah wali hakim, status perwaliannya pun sah, maka status perkawinannya pun akan sah. Selain wali nasab memberikan izin kepada wali hakim, adapula wali lainnya yang tidak memiliki ikatan sedarah atau garis keturunan lurus keatas, dapat menjadi wali nikah dengan syarat memiliki surat taukil yang diberikan oleh wali asli kepada wakil wali tersebut, selain surat tersbut dapat dilakukan dengan pengucapan wali asli dengan disaksikan oleh 2 orang saksi. Dengan adanya surat taukil atau pengucapan perwakilan wali dari wali asli kepada orang lain yang tidak memiliki hubungan darah atau garis lurus keatas, maka wakil wali tersebut sah untuk dapat menjadi wali nikah mempelai wanita, lalu mengenai status perkawinan yang diwalikan oleh wakil wali tersebut akan sah.